Molecular Dissection of the Regenerative Capacity of Forest Tree Species: Special Focus on Conifers - Díaz-Sala, Carmen (Frontiers in Plant Science, 2019)
Somatic embryogenesis and organogenesis have become leading biotechnologies for forest tree improvement and the implementation of multi-varietal forestry. Despite major advances in clonal propagation using these technologies, many forest tree species, such as conifers, show a low regeneration capacity. Developmental factors such as genotype, the type and age of the explant or tissue, and the age and maturity of the mother tree are limiting factors for the success of propagation programs. This review summarizes recent research on the molecular pathways involved in the regulation of key steps in somatic embryogenesis and organogenesis of forest tree species, mainly conifers. The interaction between auxin and stress conditions, the induction of cell identity regulators and the role of cell wall remodeling are reviewed. This information is essential to develop tools and strategies to improve clonal propagation programs for forest tree species.